Seismic demand and capacity assessment of suspended ceiling systems. (15th August 2019) - Brandolese, Sara; Fiorin, Laura; Scotta, Roberto
Highlights: The filtering action of five frames on a suspended ceiling has been analyzed. Floor response spectra have been numerically defined for five case-study buildings. Linear and non-linear analyses on suspended ceiling numerical models are performed. Results obtained from linear and non-linear analyses are compared and discussed. Abstract: In recent years, scientific interest for the study of Non-Structural Elements (NSE) has significantly increased and the importance of the seismic safety of these elements has become a widely discussed topic. Several technologies able to guarantee the seismic safety of NSE were created. In particular the sector of suspended ceiling has seen the development of different systems for achieving this purpose. Specific internal joints between profiles, perimeter brackets and bracing systems have been created to realize "anti-seismic" suspended ceilings. Several shake table tests, also defined qualifying tests, have been performed to analyze the behaviour of these systems. This work presents new original studies on seismic behaviour of suspended ceilings with an experimental fragility approach. Recently cyclic quasi-static tests have been realized at the University of Padova by means of a specifically developed experimental setup. First, experimental results were processed to define the hysteretic capacity curves of a typical metal T-Grid suspended ceiling. Then, these curves were exploited by means of numerical analyses to determine the elastic and inelastic response of the suspended ceiling installed at various levels of five multi-storey frames characterized by different vibration periods. Linear dynamic analyses of the frames subjected to 7 spectra-compatible artificial seismic signals were performed to obtain floor acceleration signals and spectra. Then three alternative numerical approaches were employed to define the seismic demand on the suspended ceiling. Using a displacement-based approach, capacity curves and elastic floor spectra were compared in the ADRS (Acceleration Displacement Response Spectrum) domain to evaluate the elastic displacements and accelerations of the suspended ceiling (Spectral Analysis). Also, Linear and Non-Linear Time-History analyses of the NSE were performed according to a cascade approach. The comparison of the seismic demands resulting from elastic, inelastic and spectral analyses is reported in the paper for each of the frames.